Leyendo a Ferrajoli: Consideraciones sobre la jurisdicción - Taruffo, Michele (2019)
The proceduralist’s attention is attracted mainly by the aspects of ferrajoli’s work dealing with the administration of justice and the characters of jurisdiction. The basic starting point is when ferrajoli stresses that jurisdiction is a secundary guarantee ensuring the judicial protection of rights. Such a guarantee has to be general, since no right actually exists without an effective protection offered by courts. In judicial contexts, justice is properly administered when legal rules are correctly applied, and the truth of the facts in issue is established, according to evidence and proof, as the classical theory of judicial decision-making claims. Some problems may arise, however, but may be easily solved when one takes into account the discretionary powers -belonging to many judges- to interpret the rules creating new rights, and the cases in which remedies precede rights. At any rate, ferrajoli rejects the so-called counter majoritarian objection outlining that the basic foundation of the judge’s role is not a popular election, but relies upon the judge’s compliance with the law